The herbicide tebuthiuron and temperature increase related to climate change can impair the photosynthesis of Oedogonium sp. (Chlorophyta) - Vilas Boas, Lucas Kortz [UNESP]; Zanini Branco, Ciro Cesar [UNESP] (FapUNIFESP (SciELO), 2024)
Freshwater habitats are among the most degraded environments, with organisms living in multi-stressor conditions. We tested the photosynthetic performance of Oedogonium sp., a freshwater green alga, after exposure to an herbicide combined with temperature increases related to climate change. Treatments were designed by combining nominal concentrations (0.00 or control, 0.05, 0.6 and 1.2 mg/L) of tebuthiuron with temperature increases projected by the Intergovernmental Panel on Climate Change for the scenarios RCP 4.5 (+2.3 ºC) and RCP 8.5 (+3.4 ºC). Treatment concentrations were determined based on i) the maximum concentration allowed by the US Environmental Protection Agency in water bodies, ii) the recommended application dosage by the manufacturer and iii) a worst-case scenario. Chlorophyll a fluorescence analysis showed that tebuthiuron concentrations of 0.6 mg/L or higher, regardless of temperature, negatively affected the photosynthetic performance of the alga, with reduced quantum photosynthetic yield associated with increased non-regulated, non-photochemical energy loss. Oxygen evolution curve analyses revealed a significant drop in the photosynthetic rate of Oedogonium sp. under both RCP scenarios in comparison to the scenario without temperature increase, with decreases ranging from 13% to 70% among treatments. Despite the clear negative effects of exposure to both stressors individually, no combined effect was observed.
Keywords: Chlorophyll a Fluorescence; Chlorophyta; Green algae; IPCC; Sugarcane crops